Lear volée: how letters killed the king. Issue 6 (3rd July 2019) - Habinek, Lianne
ABSTRACT: This essay examines the complex publishing and critical histories of King Lear to trace the fatal movement of letters across the play. Lear, perhaps more so than any other of Shakespeare's plays, is marked by violent and confusing missives, which both structure the play and undermine that very structure. Letters here expose and incite treachery, carve out crucial paths of knowledge, and ultimately damage people, power, and language itself. Drawing on theories of letter-writing from the early modern period to Poe to Derrida, this essay argues that, despite what appear to be false starts or mis-deliverings, the letter in Lear always does arrive, tragically, at its destination.